Reverse Innovation and Reverse Technology Transfer: From Made in China to Discovered in China in the Pharmaceutical Sector - Hadengue, Marine; de Marcellis-Warin, Nathalie; Warin, Thierry (Management international / International Management / Gestiòn Internacional, 2015)
The emergence of a giant like China changes the landscape. The potential localization of multinational companies' R&D centers into emerging countries changes the analytical perspective. This phenomenon moves the knowledge frontier and creates a real paradigm change in terms of innovation and technology transfer. On the one hand, we confirm the global trend of knowledge sources implied in previous studies and we demonstrate that multinationals might now choose emergent countries as a strategic place to externalize R&D. On the other hand, we go further by empirically showing the phenomena of reverse innovation and reverse technology transfer in the pharmaceutical sector.